2013
DOI: 10.1371/journal.pone.0070736
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Dopamine D2 Allosteric Modulator, PAOPA, on the Expression of GRK2, Arrestin-3, ERK1/2, and on Receptor Internalization

Abstract: The activity of G protein-coupled receptors (GPCRs) is intricately regulated by a range of intracellular proteins, including G protein-coupled kinases (GRKs) and arrestins. Understanding the effects of ligands on these signaling pathways could provide insights into disease pathophysiologies and treatment. The dopamine D2 receptor is a GPCR strongly implicated in the pathophysiology of a range of neurological and neuropsychiatric disorders, particularly schizophrenia. Previous studies from our lab have shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…In the present study, we show that CaSR internalization is negatively and positively modulated by NPS 2143 and NPS R-568, respectively. These results are in agreement with previous findings on other receptors reporting allosteric modulation of ligand-mediated internalization for the class A M1 and M4 muscarinic acetylcholine receptors (Leach et al, 2010;Yeatman et al, 2014), D2 dopamine receptor (Basu et al, 2013), cannabinoid receptor type 1 (Ahn et al, 2012;Laprairie et al, 2015), and the class C metabotropic glutamate receptor 7 (Pelkey et al, 2007). Furthermore, NPS R-568 triggered a small but statistically significant increase in constitutive CaSR internalization.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we show that CaSR internalization is negatively and positively modulated by NPS 2143 and NPS R-568, respectively. These results are in agreement with previous findings on other receptors reporting allosteric modulation of ligand-mediated internalization for the class A M1 and M4 muscarinic acetylcholine receptors (Leach et al, 2010;Yeatman et al, 2014), D2 dopamine receptor (Basu et al, 2013), cannabinoid receptor type 1 (Ahn et al, 2012;Laprairie et al, 2015), and the class C metabotropic glutamate receptor 7 (Pelkey et al, 2007). Furthermore, NPS R-568 triggered a small but statistically significant increase in constitutive CaSR internalization.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies from our lab have demonstrated the downstream effect of PAOPA on kinases, such as extracellular signal-regulated kinase 1/2 (ERK 1/2) [1]. Therefore, expression of synapsin, as observed in our studies could also be a downstream modulatory result of ERK1/2, as has been shown to occur in previous studies [22,33].…”
Section: Discussionsupporting
confidence: 82%
“…Stimulation of D1 receptor activity by agonists, or attenuation of D2 activity by antagonists, results in increased synapsin II levels [11,41]. The use of PAOPA, has previously been shown to promote internalization of the D2R, thereby decreasing overall availability of this receptor, similar to an antagonist, but with a more fine-tuned and subtle technique [1]. Reduced post-synaptic D2 activity caused by PAOPA-induced receptor internalization within the striatum, NAc and mPFC, is hypothesized to lead to decreased inhibition of cyclic adenosine monophosphate (cAMP), causing increased protein kinase A (PKA) stimulation, which eventually results in Ap-2␣ transcription factor promoted enhancement of synapsin II transcription [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a specific allosteric modulator of D 2 receptors, the peptidomimetic 3(R)‐[(2(S)‐pyrrolidinylcarbonyl) amino]‐2‐oxo‐1‐pyrrolidineacetamide (PAOPA), has been recently characterized as binding to a site on the D 2 receptor that is distinct from the endogenous ligand binding site (Tan et al ., ). PAOPA can influence several signalling and cellular events characteristic of D 2 receptor activation (Basu et al ., ), and in preclinical models, can attenuate schizophrenia‐like behavioural manifestations without causing significant motor abnormalities common with many current antipsychotics (Tan et al ., ).…”
Section: Other Developments and Emerging Trendsmentioning
confidence: 99%